Research on the Application of Thermal Protection Seal and Convenient Maintenance Materials for High-Speed Airborne Missile - Xiao Jun, Liao Zhizhong, Zhang Zhijie, Zeng Yibing, Cheng Gong (Hangkong bingqi, 2023)
In order to solve the problems of thermal protection and convenient & efficient maintenance of high-speed airborne missiles in harsh service environment, researches on two key technologies of seal for thermal protection (STP) and outfield maintenance support of thermal protection (OMSTP) of the missile bodies are carried out. Concept and relevant requirements of seal for thermal protection & convenient outfield maintenance support dual-purpose (STP-OMSTP) materials are proposed. Focusing on the needs of mass production and maintenance of the missiles, comparative tests are carried out between common repair and sealing materials matching the thermal protective coating and the STP-OMSTP materials. The results show that STP-OMSTP material has the advantages of good thermal sealing effect, quick and convenient operation, and strong environmental adaptability, which is obviously better than traditional repair and sealing materials, and is more suitable for mass production and outfield maintenance.